2020
DOI: 10.29194/njes.23040352
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Algorithm for Congestion Management in Network Based on Jitter and Time to Live Mechanisms

Abstract: As internet network developed rapidly in the past ten years, and its operating environment is constantly changing along with the development of computer and communication technology, the congestion problem has become more and more serious. Since TCP is the primary protocol for transport layers on the internet, the data transmitted via the transport protocol utilizes Vegas Transmission Control Protocol (TCP) as the congestion control algorithm, where it uses increasing in delay round trip time (RTT) as a signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…The analysis of the model showed that the algorithm had a good effect in controlling congestion, improving network throughput, reducing packet loss rate, improving network utilization, etc., and was simulated in the NS-2 network simulation platform environment. The simulation results supported theoretical analysis [ 5 ]. Casado-Vara et al proposed a new technique for processing heterogeneous temperature data collected by the IoT of smart buildings and converting them into homogeneous data as input to smart building monitoring algorithms, optimizing their performance [ 6 ].…”
Section: Related Worksupporting
confidence: 71%
See 1 more Smart Citation
“…The analysis of the model showed that the algorithm had a good effect in controlling congestion, improving network throughput, reducing packet loss rate, improving network utilization, etc., and was simulated in the NS-2 network simulation platform environment. The simulation results supported theoretical analysis [ 5 ]. Casado-Vara et al proposed a new technique for processing heterogeneous temperature data collected by the IoT of smart buildings and converting them into homogeneous data as input to smart building monitoring algorithms, optimizing their performance [ 6 ].…”
Section: Related Worksupporting
confidence: 71%
“…e simulation results supported theoretical analysis [5]. Casado-Vara et al proposed a new technique for processing heterogeneous temperature data collected by the IoTof smart buildings and converting them into homogeneous data as input to smart building monitoring algorithms, optimizing their performance [6].…”
Section: Related Workmentioning
confidence: 54%
“…When too many messages exist in the network, it will cause network performance degradation, that is, congestion occurs [1]. Congestion mainly occurs when network resources are insufficient to meet the needs of service flows, or when the distribution of network service flows is unbalanced, causing an increase in the packet loss rate of the link, increase in the delay between nodes, increase network jitter, and reduce network throughput [2], Therefore, the use of effective methods to achieve congestion control has become a hot issue in current network research. At present, many algorithms have been proposed, such as RED, REM [3], Drop Tail Queue Management, DRED [4], PI controller [5], PID controller [6], and so on.…”
Section: Introductionmentioning
confidence: 99%